On isotopic and isomorphic semirings - Abrahamyan, Liana
In this paper isotopic and isomorphic semirings is studied. It is proved that two M-isotopic semirings are isomorphic. Սույն աշխատանքում դիտարկվում են իզոտոպ և իզոմորֆ կիսաօկները: Ապացուցվում է, որ, M-իզոտոպ կիսաօղակները իզոմորֆ են: В данной работе рассматриваются изотопные и изоморфные полукольца. Доказывается, что M-изотопные полукольца изоморфны.
Keywords: Mathematics